Die compensation method of hydraulic torque converter blade based on forming simulation and spring-back prediction. (May 2015) - Liu, C. B.; Tan, Y.; Ma, W. X.; Yang, H. L.; Ge, F. M.; Chen, P. Z.
Abstract : Spring-back is an inevitable phenomenon in the forming process of sheet metal. Hydrodynamic torque converter blades are characterised by complex free-form surfaces in space, on which the forming defect occurs when spring-back exceeds the allowable size offset during the forming process. These forming defects directly affect the performances of hydrodynamic torque converters and power transmission systems. An accurate prediction method for the forming spring-back of hydrodynamic torque converter blades is not available. Therefore, it is necessary to perform accurate predictions and propose a rational design method of die forming surfaces for eliminating the influence of spring-back in forming precision. Based on CAE theories and methods of sheet metal forming, the forming process of a hydrodynamic torque converter was simulated, blade spring-back was predicted, and spring-back compensation and a die design were studied. Moreover, the study results were verified experimentally in two aspects: with simulation results through the forming of V-shaped pieces and the spring-back prediction and die compensation according to the performance indicators determined through the experiments of a hydrodynamic torque converter.